Analysis of 500 cardiovascular surgeries in Parnaíba: Results and implications (Research, Society and Development, 2024)
Objective: This study aims to analyze the outcomes of 500 cardiovascular surgeries performed in Parnaíba, focusing on success rates, complications, and clinical implications. Methodology: The research was conducted through a retrospective analysis of medical records from patients who underwent cardiovascular surgeries at the Parnaíba Hospital between January 2018 and April 2024. Results: The results indicate a high success rate and highlight areas for clinical practice improvement. Conclusion: The conclusions of this study provide support for improving health policies aimed at prevention, early diagnosis, and effective treatment of cardiovascular diseases in Parnaíba. Furthermore, this epidemiological survey contributes to the development of strategies targeted at specific risk groups, promoting improved quality of life and reducing the burden of cardiovascular diseases in the studied community.